Environmental effects of avocado farming in two hamlets of Apía, Risaralda - Hincapié-Granada, Herman Leandro; Li-Ramírez, Jade; Zuluaga-Rojas, Martha Viviana (Clío América, 2024)
The cultivation of avocados in Apía has grown from 71 hectares in 2012 to 1019 hectares in 2021, causing significant environmental changes, such as the loss of humid forests, excessive use of agrochemicals, and extreme tillage. Analyses were conducted on the deforestation rate in relation to the increase in avocado cultivation and water quality. For this, land use data from 2011 to 2016 were collected, processed with QGIS, and analyzed with R. Eight physicochemical parameters of water were also evaluated in the study areas. The results showed a decrease in "Forestry" land use and an increase in "Forestry or Tree Crops" related to avocado cultivation. Additionally, alterations in specific water parameters were observed in streams near the crops. These findings highlight the need for further studies to guide rural land use without harming natural resources.